Optimalisasi Pengelolaan Zakat Produktif Baznas Bojonegoro melalui Program Ekonomi Kreatif Z-Chicken sebagai Sistem Pengendali Kemiskinan - Eko Arief Cahyono; Dery Ariswanto; Muhammad Zaenal Abidin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Baznas of Bojonegoro Regency plays a role in assisting poverty control and empowering the community through innovative programs that utilize productive zakat schemes. The Z-Chiken program is an innovation for empowering the less fortunate by providing business mentoring in the field of crispy chicken culinary. This research aims to assess and formulate the optimization of Baznas' role through the utilization of productive zakat to control poverty in Bojonegoro Regency, with the presence of the Z-Chiken program. This study employs qualitative research methods, aiming to elucidate the utilization of zakat funds in Baznas of Bojonegoro Regency, which has a positive impact by providing greater benefits to the less fortunate in improving family economics, and to determine the extent of Baznas' contribution to poverty control in Bojonegoro Regency.The results of this study show that the active recipients of Z-Chicken assistance in this case, which amounted to 28 mustahik people, consisted of 19 mustahik who had a family income above the Poverty Line, 8 mustahik who had a family income above Had Kifayah, and 1 mustahik who had a family income above Nisab Zakat. These business activities generate average sales of 200 kg of chicken per week. The average mustahik income increased by 105.03%, namely from the initial average of Rp790,263 to Rp1,620,176 and the highest reached 280.61% or reached Rp3,007,216. So that the optimal management of productive zakat can control the poverty rate at the individual to group level through the Z-Chicken creative economy program implemented by Baznas Bojonegoro Regency.